2020
DOI: 10.1001/jamaophthalmol.2019.5823
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Open Globe Injuries in the United States From 2006 to 2014

Abstract: IMPORTANCE Open globe injuries can lead to substantial visual morbidity and lifelong sequelae. Interventions to reduce the burden of open globe injuries in the United States require a better understanding of these injuries through well-designed epidemiologic investigations. OBJECTIVE To examine the incidence, common injury mechanisms, and economic burden of open globe injuries in the United States. DESIGN, SETTING, AND PARTICIPANTS This retrospective, cross-sectional study of US nationwide emergency department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 32 publications
(55 reference statements)
6
69
0
5
Order By: Relevance
“…The corona virus pandemic has not only affected routine ophthalmic practices in multiple ways, but has also posed challenges in patients seeking ophthalmic care. [ 7 8 9 10 11 12 14 15 ] Patients presenting with routine ophthalmic check-up have reduced significantly. However, patients with ocular trauma requiring emergency ophthalmic attention were still being attended by ophthalmologists at tertiary eye care and government institutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corona virus pandemic has not only affected routine ophthalmic practices in multiple ways, but has also posed challenges in patients seeking ophthalmic care. [ 7 8 9 10 11 12 14 15 ] Patients presenting with routine ophthalmic check-up have reduced significantly. However, patients with ocular trauma requiring emergency ophthalmic attention were still being attended by ophthalmologists at tertiary eye care and government institutes.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular trauma is an important and preventable cause of visual impairment in both developing and developed countries. [ 9 ] Work-related trauma and road traffic accident remain the important causes of ocular injuries. [ 9 10 11 ] Due to the implementation of lockdown, the fear of getting infected with COVID-19, and in keeping with social distancing measures, people remained confined to their homes.…”
mentioning
confidence: 99%
“…According to the Birmingham Eye Trauma Terminology system, 1 both rupture (inside-out injury) and laceration (outsidein injury) can lead to severe damage and visual impairment. Mir et al reported an incidence of 4.49 per 100,000 population in the US from 2006 to 2014, 2 Batur et al 3.4 per 100,000 in eastern Turkey, 3 and a large population-based study in Singapore 3.7 per 100,000 population. 4 Factors associated with visual outcome after OGI repair are poor initial visual acuity (VA), retinal detachment (RD), relative afferent pupillary defect (RAPD), prolapsed vitreous, young age, blunt-force eye injury, wound size >6 mm, and no initial light reflex.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Birmingham Eye Trauma Terminology system, 1 both rupture (inside-out injury) and laceration (outside-in injury) can lead to severe damage and visual impairment. Mir et al reported an incidence of 4.49 per 100,000 population in the US from 2006 to 2014, 2 Batur et al 3.4 per 100,000 in eastern Turkey, 3 and a large population-based study in Singapore 3.7 per 100,000 population. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Open‐globe injuries are occurring more frequently and can result in poor vision prognosis even after treatment (Mir et al., 2020; Weichel, Colyer, Ludlow, Bower, & Eiseman, 2008). Unfortunately, it is difficult to develop therapeutics for this type of injury without a standardized model for evaluation, as this injury is unlike many other ocular traumas.…”
Section: Commentarymentioning
confidence: 99%